Alternative splicing in plants: current knowledge and future directions for assessing the biological relevance of splice variants - Tognacca, Rocío S; Rodríguez, Florencia S; Aballay, Federico E; Cartagena, Carla M; Servi, Lucas; Petrillo, Ezequiel (Journal of experimental botany, 2023)
Alternative splicing is an important regulatory process that produces multiple transcripts from a single gene, significantly modulating the transcriptome and potentially the proteome, during development and in response to environmental cues. In the first part of this review, we summarize recent advances and highlight the accumulated knowledge on the biological roles of alternative splicing isoforms that are key for different plant responses and during development. Remarkably, we found that many of the studies in this area use similar methodological approaches that need to be improved to gain more accurate conclusions, since they generally presume that stable isoforms undoubtedly have coding capacities. This is mostly done without data indicating that a particular RNA isoform is in fact translated. So, in the latter part of the review, we propose a thorough strategy to analyze, evaluate, and characterize putative functions for alternative splicing isoforms of interest.